2020
DOI: 10.12688/wellcomeopenres.15565.2
|View full text |Cite
|
Sign up to set email alerts
|

High dose oral rifampicin to improve survival from adult tuberculous meningitis: A randomised placebo-controlled double-blinded phase III trial (the HARVEST study)

Abstract: Background: Tuberculous meningitis (TBM), the most severe form of tuberculosis (TB), results in death or neurological disability in >50%, despite World Health Organisation recommended therapy. Current TBM regimen dosages are based on data from pulmonary TB alone. Evidence from recent phase II pharmacokinetic studies suggests that high dose rifampicin (R) administered intravenously or orally enhances central nervous system penetration and may reduce TBM associated mortality. We hypothesize that, among person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In adults with TBM, high-dose rifampicin appears to reduce mortality [ 14 ], though this finding is not universal [ 34 ], and benefit is likely to be dose-dependent. There are several phase 3 trials of 35 mg/kg underway in adults, which will provide a definitive answer to this question [ 35 ]. From a clinical pharmacology standpoint, it is logical to choose drugs and doses that achieve therapeutic concentrations at the site of disease, and rifampicin displays poor penetration into the brain and CSF [ 12 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults with TBM, high-dose rifampicin appears to reduce mortality [ 14 ], though this finding is not universal [ 34 ], and benefit is likely to be dose-dependent. There are several phase 3 trials of 35 mg/kg underway in adults, which will provide a definitive answer to this question [ 35 ]. From a clinical pharmacology standpoint, it is logical to choose drugs and doses that achieve therapeutic concentrations at the site of disease, and rifampicin displays poor penetration into the brain and CSF [ 12 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 10mg/kg dose of rifampicin, which WHO recommends for BU treatment, was selected because it is the dose used in tuberculosis treatment. Multiple tuberculosis studies have demonstrated that higher-dose rifampicin is safe and well tolerated 19,20 and comparative trials of its efficacy for tuberculosis are underway 19,21,22 . Preliminary data from mouse studies for BU suggest that higher-dose rifampicin may improve outcomes and may facilitate shortening of regimens in part because it may clear viable MU more quickly 23 .…”
Section: Any Further Responses From the Reviewers Can Be Found At The...mentioning
confidence: 99%
“…A retrospective review of clinical trial data from Indonesia suggested a higher rifampicin dosage (either oral or IV formulations) resulted in improved survival 43 . Therefore, a randomized controlled trial of high-dose oral and IV rifampicin is being launched to investigate whether this dosage achieves a higher CSF rifampicin concentration and improves outcomes 44 . Furthermore, a 2020 trial of replacing oral isoniazid and ethambutol with IV formulations resulted in significant clinical and radiographic improvement and higher rates of sputum conversion after 2 months of treatment in people with HIV with tuberculous meningitis compared with those treated with standard oral treatment 45 .…”
Section: Tuberculous Meningitismentioning
confidence: 99%